Improving Student’s Critical Thinking Skill in Mathematics Through Geogebra-Based Flipped Learning During Pandemi Covid-19: an Experimental Study - Tika Andriani; Nuriya Hazma Arifatul Ulya; Tina Putri Alfiana; Shervina Solicha; Salsa Bila Ayustiana Hafsari; Naufal Ishartono (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
w